FOLLOW UP OPINION RESEARCH -- AIRLINE SMOKING - HAMILTON FREDERICK (Tufts Archival Research Center, 2007)
Survey proposal to gauge public opinion on airline smoking. Discusses questions raised by smaller opinion research project. Presents objectives and methodology. Includes a survey.